The potential bacteriocinogenic activity of putative bacteriocins of Escherichia coli from bat guano against enterohemorrhagic E. coli strains - Chan, John Leonard R.; de Leon, Marian P.; Quimio, Julienne Maria Undine Paz; Fujiyama, Kazuhito; Sabino, Noel G.; Mendoza, Bernadette C. (2021)
This study investigated the potential bacteriocinogenic property of E. coli isolates against two EHEC strains using the Deferred Growth Inhibition, Spot-on-Lawn, andBacteriocin Sensitivity Assays, in the search for new antimicrobials against some pathogenic E. coli serotypes. Among 62 E. coli strains evaluated (sourced from native and commercial chickens, and from bat guano through UPLB-MNH), only MNH strains 1647, 1648, 1651, and 1652 showed antagonistic activity against the EHEC strains in the Deferred Assay. In the Spot-on-Lawn Assay, none of the preparations from the four isolates heated at 90˚C for 10 minutes inhibited the test strains suggesting heat sensitivity of the inhibitory substance, similar to many bacteriocins. In the Bacteriocin Sensitivity Assay, only MNH 1647 and 1651 inhibited another E. coli strain (DH5α) on LB Agar, with or without the stress inducer Mitomycin C. Significantly bigger zones of inhibition relative to the controls were observed with sonicated cell and cell-free supernatant preparations of the isolates treated with Mitomycin C. This study proved that bat guano E. coli could be potential sources of putative bacteriocins/bacteriocin-like substances against some EHEC strains and that Mitomycin C seemed to enhance the putative bacteriocinogenic activity of preparations from the bat guano isolates.
Keywords: Escherichia coli; Bats; Bacteriocins